2003
DOI: 10.1093/ndt/gfg451
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between parathyroid gland size and responsiveness to maxacalcitol therapy in patients with secondary hyperparathyroidism

Abstract: These results indicate that the responsiveness to maxacalcitol therapy of secondary hyperparathyroidism is dependent on parathyroid gland size and that the simple measurement of maximum parathyroid gland diameter by ultrasonography may be useful for predicting responsiveness to maxacalcitol treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 21 publications
1
50
0
2
Order By: Relevance
“…It is well known that, in patients with SHPT, the presence of parathyroid enlargement is a major determinant of response to treatment with vitamin D sterols (11)(12)(13). This finding is attributed to the observation that most of the enlarged glands removed from severe SHPT patients exhibit a nodular pattern of hyperplasia and decreased VDR expression (6,9,10), which could render the parathyroid glands less responsive to the biologic actions of vitamin D. In contrast, the present study showed that treatment with cinacalcet, an allosteric activator of the CaSR, is effective in suppressing PTH secretion even in patients with enlarged glands, in which the expression of CaSR is likely to be markedly decreased (7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that, in patients with SHPT, the presence of parathyroid enlargement is a major determinant of response to treatment with vitamin D sterols (11)(12)(13). This finding is attributed to the observation that most of the enlarged glands removed from severe SHPT patients exhibit a nodular pattern of hyperplasia and decreased VDR expression (6,9,10), which could render the parathyroid glands less responsive to the biologic actions of vitamin D. In contrast, the present study showed that treatment with cinacalcet, an allosteric activator of the CaSR, is effective in suppressing PTH secretion even in patients with enlarged glands, in which the expression of CaSR is likely to be markedly decreased (7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the response to vitamin D sterols is substantially reduced once parathyroid hyperplasia has progressed to the advanced nodular form, presumably because of the reduced expression of calcium-sensing receptors (CaSR) and vitamin D receptors (VDR) (6 -10). Several clinical studies suggest that parathyroid gland volume in excess of 500 mm 3 , as evaluated by ultrasonography, appears to be a useful indicator of responsiveness to vitamin D therapy (11)(12)(13). This concept is supported by the observation that surgically removed parathyroid glands weighing Ͼ500 mg usually exhibit nodular formations (3).…”
mentioning
confidence: 97%
“…Very high serum levels, as seen in this patient, could be a marker for the severity and controllability of hyperparathyroidism in these cases. Such a possibility needs to be examined in future clinical studies, especially in comparison with previously known markers, such as parathyroid size (42,45) and serum fibroblast growth factor 23 levels (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, when the gland has a volume of more than 300 mm 3 or a largest diameter of more than 1 cm, it is likely that the gland represents nodular hyperplasia. In these patients, 2HPT may be refractory to medical treatment, and PTx should be required (22)(23)(24).…”
Section: Pathogenesis Histopathology and Pathophysiology Of 2hptmentioning
confidence: 99%